Disruptive innovation in the semiconductor business, the advent of Chiplets - Camol, Giacomo; Špaček, Miroslav, 1954-; Ulrich-Diener, Florian; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The introduction of chiplet technology is about to cause a paradigm change in the semiconductor industry. Using Christensen's Theory of Disruptive Innovation as a framework, this study aims to investigate chiplets' potential to revolutionize market dynamics and industry norms. Combining qualitative and quantitative methodologies, this study employs a multi-faceted research methodology. It includes content analysis, contextual interviews with industry specialists, and thorough literature studies. In terms of technological, economic, and implementational considerations, our technique centers on comparing chiplets to conventional monolithic chip designs. Our goal is to examine the effects of chiplets on cost, performance, and market expansion in relation to the principles of disruptive innovation. In order to get a full picture of chiplet technology's function and reception in the business, interviews are planned to bring forth different points of view on the topic. By conducting this investigation, we hope to gain valuable insights into how chiplet technology could revolutionize semiconductor manufacturing and design. These findings could have far-reaching consequences for economic models and technological advancement in the high-tech industry.
Vedoucí práce: Miroslav Špaček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses